Fuzzy-proportional-integral-derivative-based controller for object tracking in mobile robots - Duc-Phuc Vuong; Trong-Thang Nguyen (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This paper aims at designing and implementing an intelligent controller for the orientation control of a two-wheeled mobile robot. The controller is designed in LabVIEW and based on analyzed image parameters from cameras. The image program calculates the distance and angle from the camera to the object. The fuzzy controller will get these parameters as crisp input data and send the calculated velocity as crisp output data to the right and left wheel motor for the robot tracking the target object. The results show that the controller gives a fast response and high reliability and quickly carries out data recovery from system faults. The system also works well in the uncertainties of process variables and without mathematical modeling.